MOLECULAR WEIGHT DISTRIBUTION OF POLLUTANTS IN LEACHATE FROM FULL SCALE LANDFILL SITE - Yaman, F. B.; Cakmakci, M.; Campagna, M.; Ozkaya, B. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2016)
The main objective of this study was to investigate the differences between the main pollutants in young and intermediate age landfill leachate in terms of molecular weight distribution (MWD). Parameters of chemical oxygen demand (COD), five day-biochemical oxygen demand (BOD5), ultraviolet-visible spectrophotometry (UV-VIS spectrum), total kjehldahl nitrogen (TKN), ammonia nitrogen (NH4-N) and colour were fractioned by membranes with the nominal pore size of 1 mu m, 0.05 mu m, 100 kDa, 50 kDa, 10 kDa, 1 kDa and 0.5 kDa. According to the MWD results appropriate treatment technology could be choosen easily. According to the MWD results the ratio of soluble fractions (< 0.5 kDa) to total COD was 34% in young leachate (YL), whereas low molecular weight (MW) fractions were dominant in intermediate leachate (IL) having this ratio of 71%. Presence of lower MW compounds in IL was also confirmed with UV-VIS absorbance spectra and its spectrum was higher than the YL. According to the specific ultraviolet absorption (SUVA) values, the organic contents of all of these processes were hydrophilic. TKN and NH4-N analysis showed that in IL all the nitrogen present is in ammoniacal form, instead in YL there is still the presence of organic nitrogen. Furthermore more than half of the TKN was less than 0.5 kDa while 6 % and 16 % TKN found in wastewater from IL and YL was higher than 1 mu m respectively. The observations of this study may provide useful criteria to choose a suitable landfill leachate treatment processes.
Keywords: Leachate age; landfill; molecular weight; SIZE DISTRIBUTION; MILL EFFLUENT; COAGULATION-FLOCCULATION; ORGANIC-COMPOUNDS; COD; FENTON; WATER; BIODEGRADABILITY; FRACTIONS; MUNICIPAL; Environmental Sciences & Ecology